Exploring Rural Social Entrepreneurship: Ukkrit Farm Hill’s Approach to Sustainable Community Development - Ruanggoon, Jirapong (CV. Literasi Indonesia, 2025)
This research explores the role of rural social entrepreneurship in promoting sustainable community development, focusing on Ukkrit Farm Hill as a case study. The study highlights the unique challenges faced by rural enterprises, such as geographical isolation and limited resources, which necessitate distinct strategies for success. Employing a qualitative case study approach, the research integrated in-depth interviews, participant observation, and document analysis to gather rich, contextual data from various stakeholders, including the farm owner, community members, and tourists. The findings reveal that Ukkrit Farm Hill effectively combines agritourism, sustainable agriculture, and community engagement, fostering economic resilience and social cohesion. This integrated approach not only enhances income diversity but also strengthens community ties and ecological stewardship. The study concludes that rural social enterprises can create sustainable solutions by leveraging local resources and fostering community involvement, thereby bridging the gap in existing literature on rural entrepreneurship and contributing to the attainment of sustainable development goals.